2020
DOI: 10.1038/s41419-020-03238-7
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric injury by KML001 in human T cells induces mitochondrial dysfunction through the p53-PGC-1α pathway

Abstract: Telomere erosion and mitochondrial dysfunction are prominent features of aging cells with progressive declines of cellular functions. Whether telomere injury induces mitochondrial dysfunction in human T lymphocytes, the major component of adaptive host immunity against infection and malignancy, remains unclear. We have recently shown that disruption of telomere integrity by KML001, a telomere-targeting drug, induces T cell senescence and apoptosis via the telomeric DNA damage response (DDR). In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 51 publications
3
53
0
Order By: Relevance
“…The model of increased oxidative stress inducing mtDNA mutations is a central mechanism commonly used to explain the aging phenomenon. Furthermore, the expression of critical proteins involved in mitochondrial biogenesis and mtDNA maintenance, including PGC-1α, ERR-α, NRF-1, and TFAM are significantly downregulated in aging cells or tissues [ 144 , 154 , 155 , 156 , 157 ]. Interestingly, age-linked associations have been made across a wide range of chronic viral infections, including but not limited to HIV, HCV, HBV, and CMV, as evidenced by increased telomere erosion and telomeric DNA damage, mitochondrial dysfunction, and cellular senescence [ 43 , 57 , 158 , 159 , 160 ].…”
Section: Discussionmentioning
confidence: 99%
“…The model of increased oxidative stress inducing mtDNA mutations is a central mechanism commonly used to explain the aging phenomenon. Furthermore, the expression of critical proteins involved in mitochondrial biogenesis and mtDNA maintenance, including PGC-1α, ERR-α, NRF-1, and TFAM are significantly downregulated in aging cells or tissues [ 144 , 154 , 155 , 156 , 157 ]. Interestingly, age-linked associations have been made across a wide range of chronic viral infections, including but not limited to HIV, HCV, HBV, and CMV, as evidenced by increased telomere erosion and telomeric DNA damage, mitochondrial dysfunction, and cellular senescence [ 43 , 57 , 158 , 159 , 160 ].…”
Section: Discussionmentioning
confidence: 99%
“…mtDNA and 8-oxoG analyses were performed as described previously ( 24 ). Briefly, genomic DNA was purified from CD4 T cells stimulated with 1ug/ml anti-CD3 and anti-CD28 as described above, and the DNA concentration was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as described previously ( 24 ). Primary antibodies included PGC1α (Cat #2178), mtTFA (Cat #8076), ERRα (Cat #13826), NRF-1 (Cat #46743), SOD1 (Cat #4266), GPx1 (Cat #3206), PCK1 (Cat #12940), and G6PD (Cat #12263) (all from Cell Signaling Technology; Danvers, MA), PGC1β (ab176328), PPARα (ab191226), and ACADM (ab110296) (all from Abcam).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that PLHIV exhibit CD4 T cell exhaustion, senescence, apoptosis, and dysfunction, despite ostensibly complete control of viral replication by ART (30)(31)(32)(33)(34)(35)(36). How T cell functions are dysregulated in ART-controlled PLHIV is incompletely understood.…”
Section: Introductionmentioning
confidence: 99%